Using Word Puzzle Media to Increase Student Interactivity Islamic Religious Education Learning - Sari, Harnum Puspita; Muslimah, Muslimah; Afifah, Neela (International Journal on Advanced Science, Education, and Religion, 2025)
Rapid technological advances require the integration of digital tools in educational practices to increase student involvement and understanding, therefore this research is important to increase student interaction in Islamic Religious Education (PAI) learning using word puzzle-based learning media at Tahfidz Al-Jamiel Elementary School, Palangka Raya. This research uses a descriptive qualitative approach. Data was collected through participant observation of Islamic Religious Education teachers, in-depth interviews with PAI teachers and school principals, and students as research informants, and documentation. The research results show that word puzzle-based learning media effectively increases student interaction in learning PAI and the use of word puzzle media. Teachers report a marked increase in student engagement. Apart from that, students expressed their level of satisfaction with the word puzzle media on the grounds that they found it easy to understand the material, and found it interesting, thus making students feel happy studying Islamic Religious Education material in Tahfidz Al-jamiel Elementary School, Palangkaraya